Design and Development an Underwater Glider using PIC for Monitoring Application - Mohd Aras, Mohd Shahrieel (2010)
This project is described a design of an underwater glider using PIC as controller. Underwater glider is a type of autonomous underwater vehicle (AUV). Underwater Glider is a technology undergoing active and rapid development that uses small changes in its buoyancy in conjunction with wings to convert vertical motion to horizontal, and thereby propel itself forward with very low power consumption. The main purpose of this project is to design and develop an underwater glider controlled by PIC. This project is categorized to three major phase which is the mechanical design concept, programming and fabrication. The design and development of the underwater glider should be having hydrodynamic characteristics, stability and buoyancy. The movement of the underwater glider is controlled by PIC controller using C language program. The underwater glider that will be produced can move forward and reverse autonomously.